Implementation fidelity of school oral health programs at a District in South Africa. - Mpho Molete; Aimee Stewart; Jude Igumbor (PLoS ONE)
Background It is important that components contributing to success of a program are well understood to ensure better outcomes and strengthen interventions. Hence the purpose of the study was to assess the level of fidelity achieved by school oral health programs in our study district and to determine elements of fidelity that predict the risk of dental decay. Methods A cross-sectional study design was utilised. A multistage sampling technique was employed to randomly select 10 schools, two grades in each school were selected and all pupils in the selected grades were included in an oral health examination. Ten oral hygienists were observed and interviewed as they carried out the activities of the program and records were reviewed. Data collection tools included an oral health examination form, and an implementation fidelity checklist. Results The average level of fidelity obtained was 40% and it was shown to be inversely correlated with levels of decay, as decay was predicted to decrease with increasing levels of fidelity. The fidelity elements that were found to directly predict the outcome of decay included duration (IRR, 0.49; p = 0.02) coverage (IRR, 0.54; p = 008), content (IRR, 1.36; p = 0.03) and age (IRR, 2.14; p = 0.00). Moderating factors of fidelity which indirectly influenced the outcome of decay included facilitation strategy, duration and age. These were predicted to reduce the risk of decay by 92%, 83% and 48% respectively. Conclusion The school oral health programs exhibited high levels of pupil coverage, however, the content of the programs offered was low (28%). Coverage was high in the context of lack of dental assistance and time. Multi-sectoral participation is therefore necessary to re-organise the program for improving implementation fidelity and bringing about quality implementation.